Somatic Embryogenesis and Plant Regeneration From Primordial Shoot Explants of Picea abies (L.) H. Karst. Somatic Trees - Varis, Saila; Klimaszewska, Krystyna; Aronen, Tuija (Frontiers in Plant Science, 2018)
The recalcitrance of adult conifer tissues has prevented vegetative propagation of trees with known and desired characteristics. Somatic embryogenesis (SE) initiation protocol, recently developed for white spruce (Picea glauca, Klimaszewska et al. 2011), was applied in order to examine the feasibility, frequency and timing of SE induction from primordial shoots (PS) of Norway spruce (Picea abies). In total, 39 genotypes were screened from 2015 to 2017 using four to six years old trees of SE origin as explant donors. Two genotypes responded: 11Pa3794 produced five proliferating embryonal mass (EM) sublines and 11Pa4066 produced 23 EM sublines. SE initiations occurred at the beginning of April, when the temperature sum (d.d.) started to accumulate, and at the end of October or beginning of November when the chilling unit (ch.u.) sum was over 500. EM sublines from both genotypes contained numerous early somatic embryos as detected by acetocarmine staining. The sublines of 11Pa4066 produced the mean of 78.6±12.8 cotyledonary somatic embryos /g FW, but 11Pa3794 produced only a few cotyledonary somatic embryos that were able to germinate. The original EM lines (from which the trees were regenerated) had produced the same number of somatic embryos in 2011 maturations, which was approximately 120 somatic embryos /g FW. Microsatellite analyses conducted with both responsive genotypes confirmed the genetic stability of the EM sublines compared with the donor trees growing in the field. SE protocol developed for white spruce PS explants was also suitable for PS of Norway spruce if the explants were in the responsive developmental stage.